The diagnostic value of a non-contrast computed tomography scan-based radiomics model for acute aortic dissection. Issue 22 (4th June 2021) - Zhou, Zewang; Yang, Jinquan; Wang, Shuntao; Li, Weihao; Xie, Lei; Li, Yifan; Zhang, Changzheng
Abstract : Abstract: To investigate the diagnostic value of a computed tomography (CT) scan-based radiomics model for acute aortic dissection. For the dissection group, we retrospectively selected 50 patients clinically diagnosed with acute aortic dissection between October 2018 and November 2019, for whom non-contrast CT and CT angiography images were available. Fifty individuals with available non-contrast CT and CT angiography images for other causes were selected for inclusion in the non-dissection group. Based on the aortic dissection locations on the CT angiography images, we marked the corresponding regions-of-interest on the non-contrast CT images of both groups. We collected 1203 characteristic parameters from these regions by extracting radiomics features. Subsequently, we used a random number table to include 70 individuals in the training group and 30 in the validation group. Finally, we used the Lasso regression for dimension reduction and predictive model construction. The diagnostic performance of the model was evaluated by a receiver operating characteristic (ROC) curve. Fourteen characteristic parameters with non-zero coefficients were selected after dimension reduction. The accuracy, sensitivity, specificity, and area under the ROC curve of the prediction model for the training group were 94.3% (66/70), 91.2% (31/34), 97.2% (35/36), and 0.988 (95% confidence interval [CI]: 0.970–0.998), respectively. The respective values for the validation group were 90.0% (27/30), 94.1% (16/17), 84.6% (11/13), and 0.952 (95% CI: 0.883–0.986). Our non-contrast CT scan-based radiomics model accurately facilitated acute aortic dissection diagnosis.